Tobacco Calcium-dependent Protein Kinases Are Differentially Phosphorylated in Vivo as Part of a Kinase Cascade That Regulates Stress Response - Witte, Claus-Peter; Keinath, Nana (The journal of biological chemistry, 2010)
In vivo phosphorylation sites of the tobacco calcium-dependent protein kinases NtCDPK2 and NtCDPK3 were determined in response to biotic or abiotic stress. Stress-inducible phosphorylation was exclusively located in the variable N termini, where both kinases were phosphorylated differentially despite 91% overall sequence identity. In NtCDPK2, serine 40 and threonine 65 were phosphorylated within 2 min after stress. Whereas Thr65 is subjected to intra-molecular in vivo autophosphorylation, Ser40 represents a target for a regulatory upstream protein kinase, and correct NtCDPK2 membrane localization is required for Ser40 phosphorylation. NtCDPK3 is phosphorylated at least at two sites in the N terminus by upstream kinase(s) upon stress stimulus, first at Ser54, a site not present in NtCDPK2, and also at a second undetermined site not identical to Ser40. Domain swap experiments established that differential phosphorylation of both kinases is exclusively determined by the respective N termini. A cell death-inducing response was only observed upon expression of a truncated variant lacking the junction and calcium-binding domain of NtCDPK2 (VK2). This response required protein kinase activity and was reduced when subcellular membrane localization was disturbed by a mutation in the myristoylation and palmitoylation site. Our data indicate that CDPKs are integrated in stress-dependent protein kinase signaling cascades, and regulation of CDPK function in response to in vivo stimulation is dependent on its membrane localization.